G368(P) Child with g6pd deficiency presented as convulsion due to acquired methemoglobinemia: case presentation. (12th March 2018) - Ismail, S; Gowda, P; Yehia, A
Abstract : Introduction: G6PD is an important enzyme in red blood cells and its deficiency renders erythrocytes susceptible to haemolysis under conditions of oxidative stress induced by oxidant drugs, ingestion of fava beans or its constituents, exposure to naphthalene, henna application, diabetic ketoacidosis and infection. It is an X-linked recessive condition, but homozygous females may also be affected. It is a common problem in some countries such the Arabian Peninsula, Turkey and the Middle-East; particularly in the Sultanate of Oman it affects 20% of male population. The main presentation is acute intravascular hemolytic anaemia and neonatal jaundice. Other nonspecific features are of chronic anaemia when there is low-grade hemolysis. Aim: Raise awareness in the recognition of uncommon precipitants of hemolysis and explore further updated discussion on the efficient management of acute intravascular haemolysis due to G6PD deficiency and its sequel as well as prevention. Case report: An 8-year-old child presented with generalised tonic clonic convulsion lasting about 20 min. On examination, he was pale and cyanosed with mild dehydration. Cardiac examination revealed a functional murmur. Abdominal examination was normal. Oxygen saturation was (SpO2 ) at admission (78%) which did not improve significantly with the administration of 10 L/min oxygen via non-rebreather mask. Urine colour was red-brown. Acute hemolytic anaemia was suspected with the association of acquired methemaglobinemia based on clinical presentation and failure of oxygen therapy to improve SpO2 . Initial investigations showed Hb 4.2 g/dL, high LDH, reticulocytes 16%, Serum ferritin 3840 ug/L and blood gases showed PaO2 92 mm Hg and methaemoglobin 17%. Urine was strongly positive for haemoglobinuria. Careful history revealed that the day before presentation, the child was exposed to naphthalene at home. Naphthalene, available as small balls of different colours, is very attractive to children to play with and even putting the mouth as sweet and this precipitated hemolysis in this case. Outcome: The child received oxygen, forced alkaline diuresis and ascorbic acid therapy, and made full recovery after 5 days hospitalisation.